\(A=\frac{1-2x}{x+3}=\frac{-2x+1}{x+3}=\frac{-2x-6+7}{x+3}=\frac{-2\left(x+3\right)+7}{x+3}=-2+\frac{7}{x+3}\)
Vì \(-2\inℤ\)\(\Rightarrow\)Để \(A\inℤ\)thì \(\frac{7}{x+3}\inℤ\)
\(\Rightarrow7⋮x+3\)\(\Rightarrow x+3\inƯ\left(7\right)=\left\{\pm1;\pm7\right\}\)
\(\Rightarrow x\in\left\{-10;-4;-2;4\right\}\)
Vậy \(x\in\left\{-10;-4;-2;4\right\}\)
ĐK:\(x\ne-3\)
Với \(A=\frac{1-2X}{X+3}=\frac{-2x-6+7}{x+3}=\frac{-2+7}{x+3}\)
A nguyên <=>\(x+3\inƯ\left(7\right)\)\(\Rightarrow x\in\left\{1;-1;7;-7\right\}\)
Vậy...